1986
DOI: 10.1111/j.1439-0329.1986.tb01054.x
|View full text |Cite
|
Sign up to set email alerts
|

Industrial air pollution and peroxidase activity in Scots pine needles – two case studies

Abstract: The peroxidase activity (EC 1.11.1.7) in homogenates from Scots pine needles {Pinus sylvestris L.) were studied in relation to needle age and sampling locations around two different sources of industrial air pollution. Increased enzyme activity was associated with both increased needle age and proximity to the emission sources. Eluorine contamination in one of the cases was not correlated with enhanced enzyme activity. Enzyme activity levels were considered in relation to variations between trees and between d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

1989
1989
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…The use of total peroxidases as bioindicators of the effects of SO 2 on conifers has been studied in both short-term (KHAN and MALHOTRA 1982) and long-term fumigation experiments (KATAINEN et al 1984;BENDER et al 1990;KLUMPP et al 1989) and in the field (NIEMTUR 1979;HUTTUNEN 1981, JOKINEN et al 1983, NYMAN 1986. Changes in peroxidase activities are thought to be reasonably sensitive means of detecting local pollution stress in Scots pine needles under field conditions as well as experimentally, and peroxidase activity has proved to be reversible in response to diminished pollution stress (NYMAN 1986).…”
Section: Introductionmentioning
confidence: 99%
“…The use of total peroxidases as bioindicators of the effects of SO 2 on conifers has been studied in both short-term (KHAN and MALHOTRA 1982) and long-term fumigation experiments (KATAINEN et al 1984;BENDER et al 1990;KLUMPP et al 1989) and in the field (NIEMTUR 1979;HUTTUNEN 1981, JOKINEN et al 1983, NYMAN 1986. Changes in peroxidase activities are thought to be reasonably sensitive means of detecting local pollution stress in Scots pine needles under field conditions as well as experimentally, and peroxidase activity has proved to be reversible in response to diminished pollution stress (NYMAN 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Exposure of pine trees to a mixture of SO, and NO.^ {c. \ 5 ppb of each gas) in an open field fumigation experiment caused a small decrease in superoxide dismura.se activity in pine needles (Wingsle & Hallgren, 1993). In different clones of Scots pine exposed to industrial air pollution increases as well as decreases in peroxidase activity were observed (Nyman, 1986).…”
Section: Introdiictionmentioning
confidence: 99%
“…The mechanism of the influence of different pollutants on plant organism is associated with oxidative damage at the cellular level (Tanaka and Sugahara 1980, Huttunen and Heiska 1988, Wingsle and H~illgren 1993. The sensitivity to different pollutants differs between plants and even between clones of the same species (Nyman 1986, Darall 1989. The advantage of the presented study was the known origin of plant material simultaneously planted on polluted and nonpolluted areas.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand in Scots pine and Norway spruce trees treated artificially with different pollutants such as SO 2 , NO 2, 03 , the activity of enzyme scavenging system such as SOD and GR was reduced (Wingsle et al 1992, Wingsle andH~llgren 1993, Kronfus et aL I998). Also in different clones of Scots pine exposed to industrial air pollution changes in PO activity were noted (Nyman 1986). Plant material for our investigations was collected from three experimental trials of Scots pine trees including 20 European provenances, established 16 years ago in Luboti, close to a phosphate fertiliser factory, in Gtog6w, close to a copper foundry and in K6rnik (20 and 100 km respectively from polluted stands), as the control stand.…”
Section: Introductionmentioning
confidence: 97%